PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TIME TOKEN TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI SEL KELAS XI MAN 1 PALEMBANG - tastin tastin; yustina Hafida; Asia Astuti (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
The purpose of this study were three, that are to determine how the learning process by using Cooperative Learning type Time Token was happend, beside that to know the abilities of creative thinking by the student, and to determine whether there was influence of learning model Cooperative Learning type Time Token towards creative thinking abilities of students in the material of cells of XI MAN 1 Palembang. The design of study used the control group pretest-posttest design with Quasi-Experimental methods or not. The samples were 66 students. According to the statistical analysis, it shows that the student’s ability for creative thinking by using Cooperative Learning model with the type of Time Token was better than the control class. It could be seen from the calculation of t test, students' ability to think creatively has showed that t test = 2,086 while t tabel with α = 5% and df = 66 – 2 = 64, 1,670 result, because t test > t table it can be concluded that H0 rejected and Ha accepted. Thus, this is reinforced by the results of the test to gain creative thinking abilities of students in the experimental class of 0,773 (high) while the control class is 0,70 (medium). The results of this study concluded that the type of Cooperative Learning model Time Token effected on students' ability to think creatively.